Durvalumab and tremelimumab combination therapy versus durvalumab or tremelimumab monotherapy for patients with solid tumors: A systematic review and meta-analysis. Issue 28 (10th July 2020) - Wang, Bi-Cheng; Li, Peng-Cheng; Fan, Ji-Quan; Lin, Guo-He; Liu, Quentin
Abstract: Background: The combination of durvalumab and tremelimumab results in clinical benefit, with a tolerable safety profile in patients with solid tumors. Objective: To evaluate the efficacy and safety of durvalumab in combination with tremelimumab compared with either drug alone. Methods: The online databases (PubMed, Web of Science, EMBASE, and Cochrane Library) were searched for potential clinical studies up to Nov 26, 2019. Eligible studies were prospective and registered clinical trials. Pooled odds ratios for objective response rate and disease control rate and pooled risk ratios for treatment-related adverse events were meta-analyzed. A random-effect model was used due to the synthesis of different cancer types. Results: Overall, 5 studies were eligible for systematic review, 3 of which were further meta-analyzed. Durvalumab plus tremelimumab was superior to tremelimumab monotherapy in improving disease control rate in head and neck squamous cell carcinoma. However, there were no significant differences between dual immunotherapy and mono-immunotherapy in pancreatic ductal adenocarcinoma and gastric and gastroesophageal junction adenocarcinoma. Additionally, pooled analyses illustrated that no significant differences in treatment-related adverse events were displayed between the 2 groups. Conclusion: Durvalumab and tremelimumab combination therapy had a good safety profile and resulted in clinical benefit in head and neck squamous cell carcinoma. Future explorations are needed to further confirm the application of durvalumab plus tremelimumab.